1971
DOI: 10.1590/s0074-02761971000200005
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasmose em primatas não humanos: II - Tentativas de infecções experimentais em Macacca mulatta, Cebus apella e Callithrix jacchus; e pesquisa de anticorpos em várias espécies de platyrrhinus

Abstract: Após uma revisão da toxoplasmose experimental em primatas não humanos, são relatadas as tentativas, sem êxito, para provocar toxoplasmose aguda e fatal em dois rhesus (Macacca mulatta), um infante e outro jovem, por inoculação e reinoculação de uma amostra humana, usando diferentes vias e doses maciças e ainda com a ministração de decametasona. Do mesmo modo, não teve sucesso a tentativa para induzir a doença fatal em um Cebus apella adulto, pela via peritoneal. Porém a toxoplasmose-infecção nesses 3 animais, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1974
1974
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Of interest is the observation that the Cebus was routinely fed raw meat. The private owner also had 2 black-striped capuchins ( Cebus libidinosus ) that were not ill but had dye test titres of 1:64 (Nery-Guimarães et al 1971).…”
Section: Clinical Toxoplasmosis In Other Animalsmentioning
confidence: 99%
“…Of interest is the observation that the Cebus was routinely fed raw meat. The private owner also had 2 black-striped capuchins ( Cebus libidinosus ) that were not ill but had dye test titres of 1:64 (Nery-Guimarães et al 1971).…”
Section: Clinical Toxoplasmosis In Other Animalsmentioning
confidence: 99%
“…In dogs experimentally infected with Toxoplasma oocysts, Oppermann [19] observed parasitemia between the 9th and 12th days. Among the primates, Nery-Guimaraes and Franken [18] checked for parasitemia in two experimentally infected rhesus between 10 and 66 days and failed to detect it. Draper et al [3] fed oocysts to chimps and found parasitemia in one of the two animals on day 7.…”
Section: Discussionmentioning
confidence: 99%
“…[8]; liver and spleen in M. mulatta [18]; and lymph nodes and muscles in chimps [3], All but the last of these were found during the acute phase of the infections. In our experiment, Toxoplasma organisms were isolated by mouse inoculation of brain and heart tissues of chronically infected monkeys.…”
Section: Discussionmentioning
confidence: 99%
“…The private owner also had two black‐striped capuchin that were not ill but had T. gondii dye test antibody titers of 1:64 [Nery‐Guimarães et al, ]. Nery‐Guimarães and Franken () reported low levels (1:2–1:8) dye test T. gondii antibodies in 18 of 22 captive Sapajus sp. in Rio de Janeiro.…”
Section: Introductionmentioning
confidence: 99%